Content-Based Instructional Module in Teaching Oral Communication in Context for Grade 11 Science, Technology, Engineering, and Mathematics (STEM) Senior High School Students - Magsino , Milcah Shem (Journal of Interdisciplinary Perspectives, 2025)
This study developed a content-based instructional module for teaching Oral Communication in Context to Grade 11 STEM Senior High School students. It aimed to (1) determine students’ communicative needs through needs analysis, (2) develop an instructional module based on these needs, (3) evaluate its quality, and (4) assess its acceptability to students. Using a descriptive method with purposive sampling, 30 respondents participated in the needs analysis, 32 in development and evaluation, and 161 in the acceptability test. Findings revealed that students’ preferred fields of study included Engineering, Nursing, Architecture, Medicine, and Biology. Desired topics emphasized decision making, critical analysis, independent thinking, problem solving, and negotiation. In skills development, public speaking ranked highest for speaking, sentence construction, and cohesion for reading, summarizing for writing, and listening for main ideas. The module evaluation by teachers and material developers showed high ratings across objectives (3.87), content (3.85), format and language (3.84), activities (3.80), and assessment (3.89). Students rated it acceptable in content (3.44), format and language (3.46), activities (3.43), and highly satisfactory in assessment (3.51). Overall, the module was positively received and ready for validation and try-out. Teachers are encouraged to use content-based activities to enhance students’ communicative competence further.